Model testing of foundations for offshore wind turbines - Villalobos Jara, F; F. A. Villalobos Jara (2006)
Suction caissons are a new foundation option for offshore wind turbines. This thesis is focussed on the behaviour of suction caisson foundations in sand and in clay during installation, and under subsequent vertical and combined moment-lateral loadings. The research is based on extensive experimental work carried out using model scaled caissons. The analysis of the results allowed the determination of parameters for hyperplasticity models. Model caissons were vertically loaded in loose and dense sands to study in service states and plastic behaviour. Bearing capacity increased with the length of the caisson skirt. The bearing capacity formulation showed that the angle of friction mobilised was close to the critical state value for loose sands and close to those of peak values due to dilation for dense sands. The vertical load increased, though at a lower rate than during initial penetration, after large plastic displacements occurred. A hardening law formulation including this observed behaviour is suggested. In sand the installation of caissons by suction showed a drastic reduction in the net vertical load required to penetrate the caisson into the ground compared with that required to install caissons by pushing. This occurred due to the hydraulic gradients created by the suction. The theoretical formulations of the yield surface and flow rule were calibrated from the results of moment loading tests under low constant vertical loads. The fact that caissons exhibit moment capacity under tension loads was considered in the yield surface formulation. Results from symmetric and non symmetric cyclic moment loading tests showed that Masing’s rules were obeyed. Fully drained conditions, partially drained and undrained conditions were studied. Caisson rotation velocities scaled in the laboratory to represent those in the field induced undrained response for relevant periods of wave loading, a wide range of seabed permeabilities and prototype caisson dimensions. Under undrained conditions and low constant vertical loads the moment capacity of suction caissons was very small. Under partially drained conditions the moment capacity decreased with the increase of excess pore pressure. In clay, vertical cyclic loading around a mean vertical load of zero showed that in the short term the negative excess pore pressures generated during suction installation reduced vertical displacements. The yield surface and the flow rule were determined from moment swipe and constant vertical load tests. The moment capacity was found to depend on the ratio between the preload Vo and the ultimate bearing capacity Vu. Gapping response was observed during cyclic moment loading tests, but starting at smaller normalised rotations than in the field. The hysteresis loop shape obtained during gapping cannot be reproduced by means of the Masing’s rules.